Substitution of Mocaf Flour (Modified Cassava Flour) on the Physicochemical and Sensory Characteristics of Purple Sweet Potato Steamed Brownies (Ipomoea batatas L.) - Tarigas, Darsi Nian; Priyono, Suko; Hartanti, Lucky (FoodTech: Jurnal Teknologi Pangan, 2025)
Brownies are a type of family cake that is brown in color and does not expand, but has a moist (moist) texture, the top of the brownies has a dry texture, has a sweet taste and a distinctive chocolate aroma. Brownies can be divided into two types, namely steamed brownies and brownies. Mocaf flour has advantages in physiological effects such as preventing colon cancer, has a hypoglycemic effect, but mocaf also has disadvantages, namely its protein content is low and does not have gluten content like wheat flour, purple sweet potato paste was added in this study because the natural color pigments contained in purple sweet potatoes can provide an attractive color to the resulting brownie products. This study is expected to provide information to develop the use of local food ingredients that have not been popular to be developed in order to create product innovation and have economic value. This study used a Randomized Block Design (RAK) consisting of 5 levels of treatment and repeated 5 times, so that 25 experimental units were obtained. The levels of mocaf flour and wheat flour were: 90:10, 70:30, 60:40, 50:50, 40:60. The parameters observed in this study were water content, ash content, fat content, protein content and carbohydrates. The results showed that the best treatment of steamed purple sweet potato brownies based on the effectiveness index was the formulation of 60% mocaf flour to 40% wheat flour which had physicochemical characteristics in the form of water content of 38.81%, ash content of 1.93%, fat content of 9.54%, protein content of 17.30%, carbohydrate content of 32.42%, color 3.70 (like), aroma 3.73 (like), taste 4.20 (prefer), and texture 3.97 (like).